Physiologically healthy nutrition, the importance of proteins. (Eurasian Journal of Humanities and Social Sciences, 2025)
Physiologically healthy nutrition is a balanced and proper nutrition system in accordance with the natural needs of the human body. This nutrition method ensures a healthy life by providing the body with a sufficient amount of energy, nutrients and vitamins.